Solar dew removal switch cabinet - LU SHUANGJIA; WANG JUNXING; LIN XIANNA; LIN XIANHE; WANG YANG; BAO XIAOYING; ZHOU YONGLIN; BAO ZHEYING (2022)
The utility model discloses a solar dew-removing switch cabinet, which comprises a cabinet body, an exhaust fan and an air inlet fan are arranged on one side of the cabinet body, the exhaust fan is positioned above the air inlet fan, a solar panel is arranged at the top of the cabinet body, a storage battery is arranged in the cabinet body, an automatic tracking device is arranged between the solar panel and the cabinet body, and the solar panel is positioned above the storage battery. An electric heating wire is arranged at the position of the air inlet fan, the exhaust fan, the air inlet fan and the electric heating wire are all electrically connected with the storage battery, a humidity sensor and a temperature sensor are arranged in the cabinet body, solar energy is absorbed through the solar panel to supply power to the exhaust fan and the air inlet fan, and energy is saved; through heating of the electric heating wire, moisture is prevented from condensing into dew in the cabinet body, influence on elec